Membentuk Jiwa Kewirausahaan pada Anak Usia Dini melalui Kegiatan “Market Day” - Asri Prasetyaningsih (Program Studi PGRA, 2016)
Early childhood education is the level of education before primary education which is an approach to development that is intended for children from birth up to the age of six years are accomplished by providing stimulation of education to help the growth and development of the physical and spiritual so that children have the readiness to enter education further, held in formal, non-formal and informal according to Indonesian Wikipedia, the free encyclopedia. Forming the entrepreneurial spirit in early childhood through play is a form of implementation of the most fundamental and is done through a continuous process so that the child will hone their talents and potentials. Through various activities in the learning process of children will be sensitive to the environment that would take him to the ideals that he wants. Besides, teachers should also provide facilities and infrastructure in guiding and shaping the entrepreneurial spirit so that children will not be doubt in choosing what is best for him. Market Day is one of education that aims to provide an understanding and awareness is relatively intact about life, forming the structure of emotion and mentality are more stable, and develop attitudes daily more enlightened from time to time